The effect of decreasing sorghum amylose content on steam-flaking production characteristics - Froetschner, J.R.; Hancock, Joe D.; Behnke, Keith C.; McKinney, Leland J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This experiment demonstrated no advantage in using a waxy sorghum over a conventional sorghum for steam flaking. Even though the waxy variety had a slight increase in in-vitro gas production after flaking, the benefit was outweighed by the significant increase in energy requirement and significant decrease in production rate during processing.
Keywords: Beef; Waxy sorghum; Steam flaking